Flat-plate collector construction and system configuration to optimize the thermosiphonic effect - Kalogirou, Soteris A. (My University, 2014)
Thermosiphon systems heat potable water or heat transfer fluid and use natural convection to transport it from the collector to storage. This type of technology is applied extensively in countries with good sunshine potential. One such example is Cyprus, which is currently the leading country in the world with respect to the application of solar water heaters for domestic applications, with more than 93% of the houses equipped with such a system. The performance of such a system depends on many factors including the collector construction and the arrangement of the system, mainly with respect to the distance between the top of the solar collector and the bottom of the storage tank and the solar collector slope, which affects both the energy collected and the hydrostatic pressure of the system. A typical system in Cyprus uses 3m2 of collectors, 160lstorage, its collectors are usually inclined at 45° from horizontal and has 15mm copper riser tubes and header tubes with a diameter of 28mm. The collector absorber plate is also made from copper. The main objective of this paper is to investigate through modeling and simulation possible configurations, which will optimize the performance of the system. For this purpose, a number of riser and header tube diameters were considered ranging from 6mm to 35mm, slopes from 20° to 90° and distances between the top of the collector to the bottom side of the storage tank ranging from ±15cm. The system is modeled using TRNSYS and simulated with the Typical Meteorological Year (TMY) of Nicosia, Cyprus. The results showed that the best-optimized system is obtained for small header and riser pipe diameters and very close performance is obtained for various combinations. Therefore, the decision on the optimum system should depend on cost issues, which are currently very important because of the increased price of copper and operational problems depending on the hardness of the water in the area of installation, which could cause scale deposits that could clog the riser pipes. The optimum slope is found to be equal to the latitude plus 10°, i.e., 45°, although a smaller slope does not affect the performance a lot, and the optimum distance between the top of the collector and the bottom of the storage tank is-15cm. These findings should prove valuable for the collector and systems designers and manufacturers.
Keywords: Collector slope; Header and riser pipe diameters; System configuration; Thermosiphonic solar water heaters